TikTokers Turned Influencers: iGeneration’s Perceptions toward their 'Preferred' TikTok Influencers to Follow - Balatbat, Maricel S.; Cabungcal, Miguel Angelo C.; Centeno, Mica Beatrize C.; Fabrigar, Jose Rapahel G.; Garfin, Alejandra Beatrize M.; Blasa-Cheng, Angelique C.; Vergara, Raymond Allan G.; Vergara, Kimberly Christie S. (Future Science / FSH-PH Publications, 2023)
Purpose – This study explored the potential factors the iGeneration considers before intending to follow TikTok influencers, assessed their behavioral response as an outcome of the intention, and examined the impact TikTok influencers had on their potential followers. Design/methodology/approach – The researchers used a convergent mixed-parallel design to interpret data gathered from interviews and surveys with the quantitative data analyzed through the Jamovi software. This study used the philosophies of pragmatism and interpretivism. Findings – TikTok users considered perceived added value to personal lifestyle and perceived hedonic experience the most compared to other antecedents tested. The researchers classified them according to the findings and arrived at three (3) distinct categories, transitioning from intention to behavior; (A) Nonchalant, (B) Serious, and (C) Adaptive. Research Limitations/Implications – The scope and delimitations of this study only involved students currently enrolled in De La Salle University, between 17 to 24 years old. The researchers used purposive and convenience sampling to acquire respondents for the Google Forms survey and Zoom interviews. Practical and Social Implications – This study has implications for business and e-commerce, especially in the current commercial climate where influencer marketing is gaining popularity. Furthermore, it can help enterprises look for suitable influencers who can positively impact their branding to the public. Originality/Value – This study addressed the gap in the literature on TikTok users and their behavior toward the consumption of influencer content, with the increasing popularity of TikTok as a social platform and the growth of influencers as online opinion leaders.